Peningkatan Minat Belajar Al-Qur'an Anak-anak melalui Program Bimbingan Mengaji di Masjid Nurul Iman Lingkar Timur - Rizkia Aulia Permatasari; Oktavia Veby Ramawadhani; Marco Berliandra; Septi Supita; Pretty Camelia (PT. Hasba Edukasi Mandiri, 2026)
This community service program aimed to increase children's interest in learning the Qur'an through a Qur'an reading guidance program at Nurul Iman Mosque, Lingkar Timur. Based on asset mapping using the Asset-Based Community Development (ABCD) approach, the main issue identified was not the lack of facilities but the limited variety of teaching methods. The mosque possesses significant community assets, including the active participation of mosque youth, enthusiastic women's study groups, and strong support from the mosque management and parents. The program was implemented through four stages: Discovery (asset mapping), Dream (exploring the community's vision), Design (collaborative program planning), and Destiny (implementation and sustainability commitment). The results demonstrated significant improvements, with children's attendance increasing by 175%, learning interest scores rising from 3.9 to 8.6, and Qur'an reading skills improving substantially, as four children who were previously unable to recognize the Arabic letters (Hijaiyah) became fluent readers. Furthermore, the social impacts included the revitalization of the mosque's role as a center for character education and the strengthening of social capital within the Lingkar Timur community. The Qur'an reading guidance program proved to be an effective and sustainable asset-based community empowerment model.